Access to archives of organizations of faith traditions. Issue 1 (January 2018) - von Rütte, Hans
Abstract : The Principles of Access to Archives, adopted in 2012 by the International Council on Archives (ICA), address the basic right of the public to access archives, and the responsibility of archivists and of other stakeholders of archives to ensure their permanent availability. These Principles are a solid and much-needed foundation to guarantee that historians, who are in search of relevant sources for their research, have independent access to archives. To date, the application and impact of the Principles has been weak, and generally limited to archives that hold documents on human rights violations. Looking beyond this important focus, this paper considers how archives of churches and faith organizations would be well-served by following the Principles of Access to Archives as a guideline of best practices, using the World Council of Churches (WCC) to illustrate the importance of open access to archives of faith traditions, which preserve important historical material.